2020
DOI: 10.1016/j.gie.2020.03.2477
|View full text |Cite
|
Sign up to set email alerts
|

Mo1283 LEARNING CURVE OF TRANSORAL INCISIONLESS FUNDOPLICATION: A SINGLE ENDOSCOPIST EXPERIENCE

Abstract: TXTransoral Incisionless Fundoplication (TIF) is a minimally invasive endoscopic technique proven to be safe and effective for treating Gastroesophageal Reflux Disease (GERD) in selected patients. The learning curve of this technique has not been studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“… 13 , 14 As of 2019, it has been reported that more than 22,000 patients have undergone TIF. 13 An abstract by Brewer Gutierrez et al 15 reported their experience with the learning curve of TIF, which showed a progressive decrease in the total procedure time with experience. They also reported that endoscopists required at least 23 procedures to achieve procedure times <1 hour.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 14 As of 2019, it has been reported that more than 22,000 patients have undergone TIF. 13 An abstract by Brewer Gutierrez et al 15 reported their experience with the learning curve of TIF, which showed a progressive decrease in the total procedure time with experience. They also reported that endoscopists required at least 23 procedures to achieve procedure times <1 hour.…”
Section: Discussionmentioning
confidence: 99%